All Teeth and Claws: Constructing Bears as Man-Eating Monsters in Television Documentaries - Michael Fuchs (European Journal of American Studies)
Since the mid-1980s televised wildlife documentaries have become increasingly spectacular. In particular, documentaries revolving around large predators have not just proliferated, but supported entire networks, as evidenced by Discovery’s Shark Week, which has enjoyed a phenomenal success since its introduction in 1988. Shark Week, as Matthew Lerberg (2016) has shown, epitomizes the representational reductionism which operates across media—sharks are nothing but fin and jaws. Drawing on audiovisual conventions established by Jaws, sharks tend to be depicted as monsters—even in programs with didactic and/or conservationist goals. In this article, I explore representations of another large predator family, bears, in two Animal Planet documentaries. As I show, the monstrous bears embody human anxieties, but they also invite human sympathy, as human beings have turned them into monsters.